Sonic versus ultrasonic activation for the cleaning of the root canal after post space preparation: an in vitro study. - René Carrasco; Ricardo Román; Makarena Ojeda; Carolina Vergara (Universidad de Concepción., 2015)
Objective: To compare the efficacy of 3 intracanal cleaning protocols used before cementation of prosthetic posts. Material and Methods: 40 anterior teeth received endodontic treatment in hand, using lateral condensation technique. After two weeks, gutta-percha was appropriately removed from the teeth to get the necessary space to install a post. Then, teeth were randomly divided into groups; root surface was treated with chlorhexidine (CHX) activated by ultrasound (US) (group I), with chlorhexidine activated by sonic instrumentation (S) (group II), chlorhexidine without activation (group III) and without treatment (group IV). All teeth were fractured longitudinally getting 2 sections. The middle third of the root canal was microphotographed with a scanning electron microscope (SEM) and the contaminated surface was measured using detritus with ImageJ 1.47. It was analyzed with Kruskal-Wallis-test using GraphPad Prism 5.01. Results: The median percentage of contaminated area of Group I was 20.06%, Group II, 19.3%; Group III, 36.05%; and Group IV, 56.45%. Conclusion: There are significant differences among different intracanal cleaning protocols in the removal efficiency of detritus from the root canal, being the activated protocols the most effective ones.